2012
DOI: 10.1007/s11999-012-2413-5
|View full text |Cite
|
Sign up to set email alerts
|

Precision and Accuracy Measurement of Radiostereometric Analysis Applied to Movement of the Sacroiliac Joint

Abstract: Background Different techniques have been used to quantify the movement of sacroiliac (SI) joints. These include radiostereometric analysis (RSA), but the accuracy and precision of this method have not been properly evaluated and it is unclear how many markers are required and where they should be placed to achieve proper accuracy and precision. Purpose The purpose of this study was to test accuracy and precision of RSA, applied to the SI joint, in a phantom model and in patients. Methods We used a plastic pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 17 publications
4
39
1
Order By: Relevance
“…A number of studies have made attempts to describe SIJ movements both qualitatively and quantitatively (Weisl, 1955;Egund et al 1978;Lavignolle et al 1983;Miller et al 1987;Rothk€ otter & Berner, 1988;Sturesson et al 1989Sturesson et al , 1999Sturesson et al , 2000aVleeming et al 1989Vleeming et al , 1992aSimonian et al 1994a;Jacob & Kissling, 1995;Kissling & Jacob, 1996;Wang & Dumas, 1998;Kibsg ard et al 2012Kibsg ard et al , 2014bLindsey et al 2014). The common observation is that its overall movement is multi-dimensional and held within a small range, but to a highly variable extent among individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have made attempts to describe SIJ movements both qualitatively and quantitatively (Weisl, 1955;Egund et al 1978;Lavignolle et al 1983;Miller et al 1987;Rothk€ otter & Berner, 1988;Sturesson et al 1989Sturesson et al , 1999Sturesson et al , 2000aVleeming et al 1989Vleeming et al , 1992aSimonian et al 1994a;Jacob & Kissling, 1995;Kissling & Jacob, 1996;Wang & Dumas, 1998;Kibsg ard et al 2012Kibsg ard et al , 2014bLindsey et al 2014). The common observation is that its overall movement is multi-dimensional and held within a small range, but to a highly variable extent among individuals.…”
Section: Discussionmentioning
confidence: 99%
“…One underlying assumption for these therapies is that they influence SIJ pain as a consequence of altering motion. Sound scientific evidence of such alterations is still pending, and there is conflicting data for reference values of physiological movement (Weisl, 1955;Lavignolle et al 1983;Jacob & Kissling, 1995;Kissling & Jacob, 1996;Sturesson et al 1999Sturesson et al , 2000aKibsg ard et al 2012Kibsg ard et al , 2014bEgund & Jurik, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, combining all the data from published studies employing RSA and appropriate markers, the maximum sagittal rotation of the SIJ never exceeds 3.6°and translation of the joint never exceeds 2 mm (Kibsg ard et al 2012). Amalgamating these data with the observation that osteophytosis in women, regardless of age, is rare (1.83% of females) and not very common in men (12.27%; Dar et al 2008), it therefore appears that small SIJ movements are present, even at an advanced age (Vleeming et al 1992).…”
Section: Specific Itemsmentioning
confidence: 97%
“…Sturesson responded to the critique by explaining that the RSA technique enables optimal spatial contribution of the implanted markers, resulting in highly precise measurements. Moreover, a recent article has reported that when RSA is applied correctly, the method is reproducible and can be regarded as the gold standard in measuring small joint movements in orthopedic research (Kibsg ard et al 2012). …”
Section: General Commentmentioning
confidence: 99%
“…Several techniques have been used to accurately quantify the innominate bone kinematics, while using either multiple radiographs (Mens et al, 1999) or roentgen stereophotogrammetric analysis with implantation of radio-opaque markers (Sturesson et al, 1989;Kibsgard et al, 2012). While these techniques are highly accurate for investigating joint ranges of motion (ROM) between the two test positions, they are not appropriate for investigation of patterns or trends of joint motion as they cannot be performed in real time.…”
Section: Introductionmentioning
confidence: 99%